الأحكام الشرعية لعقود الخيارات المالية المعاصرة: دراسة فقهية - اليحيى، بندر بن عبدالعزيز بن إبراهيم (جامعة القصيم, 2019)
تعد عقود الخيارات أحد أهم أنواع المشتقات المالية المستخدمة في إدارة التحوط من المخاطر المالية، التي تعطي المستثمر فيها فرصة مهمة لتقليل المخاطر التي يمكن أن يتعرض إليها؛ حيث إن عقود الخيارات كغيرها من المشتقات المالية تشتق قيمتها من قيمة واحدة أو أكثر من الأصول السلعية أو الأصول المالية المرتبطة بها، وفي ظل النمو الكبير للتعامل بعقود الخيارات، ودخولها بعض الأسواق المالية الإسلامية من جهة، وتفاقم المخاطر المرتبطة بها من جهة أخرى، التي من شأنها تهديد اقتصاديات الدول، وليس فقط تهديد مؤسسة أو بنك معين؛ فقد أصبح من الأهمية بمكان بيان حقيقة هذه العقود وأحكامها الشرعية، والسعي لاقتراح بدائل لها في ضوء مقررات التشريع الإسلامي. وعليه؛ فإن الإشكال المطروح الذي يراد معالجته في هذا البحث، هو: ما الأحكام الشرعية لعقود الخيارات المالية؟ وهل يمكن تحصيل الأهداف المشروعة لعقود الخيارات باستخدام أدوات شرعية؟ وقد قسمت بحثي هذا إلى: مقدمة، وتمهيد، ومبحثين، تناولت في المبحث الأول: عقود الخيارات: تعريفها، وخصائصها، وأنواعها. وخصصت المبحث الثاني لبيان التكييف الشرعي لعقود الخيارات المالية المعاصرة، من حيث بيان الأحكام الشرعية لهذه العقود، كما عرضت إلى بيان أحكام تصفية عقود الخيارات وتسويتها، وأحكام المضاربة على الخيارات وبدائلها الشرعية، وانتهيت إلى جملة من النتائج، أهمها: 1- أن عقود الخيارات أداة من أدوات الاستثمار المستحدثة، يستخدمها المستثمرون وسيلة تحوطية للحماية من مخاطر تغيير أسعار الأوراق المالية وأسعار العملات، وطريقة لتعظيم أرباحهم بأقصر الطرق وأسرعها، من خلال المضاربة على فروق الأسعار. 2- نظرا لما تحتويه عقود الخيارات من محاذير شرعية وشروط فاسدة، ونظرا إلى أن المعقود عليه ليس مالا، ولا منفعة، ولا حقا ماليا يجوز الاعتياض عنه؛ فإنها عقود محرمة لا يجوز تداولها لا بيعا ولا شراء.
Option contracts are among the most important types of financial derivatives used to manage hedging against financial risks, in which investors are given a significant opportunity to reduce the risk they may be exposed to. This is due to the fact that option contracts, like other financial derivatives, derive their value from one or more of their associated commodity assets or financial assets. In light of the significant growth of options contracts dealings and their introduction to some Islamic financial markets on the one hand, and the aggravation of associated risks on the other hand, which would threaten the economies of countries, not only particular institutions or banks, it has become important to demonstrate the essence of these contracts and how they are viewed in Shari'ah, and attempt to propose alternatives to these contracts in light of the requirements of Islamic legislation. Therefore, this paper aims to address the following problematics: what are the provisions of Shari'ah concerning financial options contracts? Can the legitimate objectives of options contracts be obtained by using legitimate tools? This paper is divided into a preface, introduction, and two sections. The first section deals with options contracts, including their definition, characteristics and types. The second section states the legal adaptation of contemporary financial options contracts, in terms of the Shariah provisions of contemporary financial options contracts. It also indicates the provisions for the liquidation and settlement of options contracts, and the provisions of speculation in such contracts and their legal alternatives. The paper has come out with several conclusions, the most important of which are as follows: 1. Options contracts are an innovative investment tool, used by investors as a precautionary measure to protect them against the risks of the changing prices of securities and currencies, and as a way to maximize their profits via the shortest and quickest route through speculation in price differentials. 2. Since options contracts contain legal caveats and corrupt terms, and given that the subject of the contract is neither money, nor benefit, nor a financial right that may be substituted, these are Haram (illegal) contracts that may not be traded neither by sale nor by purchase
Keywords: الأحكام الشرعية -- الفقه الإسلامي -- الأسواق المالية -- المشتقات المالية